SEJARAH TURUNNYA AL-QUR’AN PENUH FENOMENAL (MUATAN NILAI-NILAI PSIKOLOGI DALAM PENDIDIKAN) - Yusron Masduki (Medina-te : Jurnal Studi Islam, 2017)
The phenomenon of receiving the revelations of the Qur'an shocked many. This can be seen from the role of Prophet Muhammad SAW prepared gradually, a time full of indecisiveness in seeing the events, phenomena, and vision of the existing view, also participate in preparing the maturity of his soul, where the angel Jibril repeatedly introduce himself. Archangel Gabriel for the first time to introduce himself when he berkhalwat in Hira Cave, Gabriel asked Muhammad SAW read, and he rationed do not know, do not know what to read, until the angel Gabriel repeats three times, and he replied in a state completely confused Fear before knowing the unforeseen prophethood and first heard the Qur'an, its psychological charge in the education of mankind.